Tinjauan Umum Potensi Sumberdaya Monasit di Daerah Ketapang Kalimantan Barat - Soetopo, Bambang; Syaeful, Hery; Marzuki, Anang; Sudarto, Slamet (EKSPLORIUM, 2011)
Monazite is one of the minerals that contain thorium and rare earth element (RE). Geologically at study area there are indications radioactive minerals that is monazite in alluvial sediments sourced from granitic rocks. The purpose of this study to obtain information of geological character, distribution and mining of mineral resource potential of radioactive materials and availability information area prospects containing monazite detailed in order to further follow-up exploration. The results in Pangkalan Telok Base Areas, Ketapang show that the geological rock unit consists of clay unit, Sangiyang granite unit, Sukadana granite unit, diorite unit, basalt unit and alluvial. Due process of weathering, transport and sedimentation, then the granitic rock, monazite minerals and zircon separated and deposited as alluvial directional spread North – South. This is reflected from the radioactivity measurements of heavy minerals, which ranged between 100 – 700 c/s and value of soil radiometric of 100 – 300 c/s. Radiometry values are included in the eastern part of which is predicted to originate from Sukadana granite. Patterns of distribution of soil radiometry, heavy mineral and content of U and Th have the relative direction of northwest – southeast, at area of 91,511,200 m2 has an average Th content of 1.97 to 46.98 ppm/gram.